Distinct Oceanic Microbiomes From Viruses to Protists Located Near the Antarctic Circumpolar Current - Flaviani, Flavia; Schroeder, Declan C.; Lebret, Karen; Balestreri, Cecilia; Highfield, Andrea C.; Schroeder, Joanna L.; Thorpe, Sally E.; Moore, Karen; Pasckiewicz, Konrad; Pfaff, Maya C.; Rybicki, Edward P. (Frontiers in Microbiology, 2018)
Microbes occupy diverse ecological niches and only through recent advances in next generation sequencing (NGS) technologies has the true microbial diversity been revealed. Furthermore, lack of perceivable marine barriers to genetic dispersal (i.e. mountains or islands) has allowed the speculation that organisms that can be easily transported by currents and therefore proliferate everywhere. That said, ocean fronts are now commonly being recognised as barriers for microbial dispersal. Here we analysed samples collected from a total of six stations, four located in the Indian Ocean and two in the Southern Ocean, i.e., either side of the Antarctic Polar Front (APF). Amplicon sequencing was used to characterise both prokaryotic and eukaryotic plankton communities, whilst shotgun sequencing was used for the combined environmental DNA (eDNA), microbial eDNA (meDNA) and viral fractions. We found that Cyanobacteria dominated the prokaryotic component in the South-West Indian Ocean, while γ-Proteobacteria dominated the South-East Indian Ocean. A combination of γ- and α-Proteobacteria dominated the Southern Ocean. Alveolates dominated almost exclusively the eukaryotic component, with variation in the ratio of Protoalveolata and Dinoflagellata depending on station. However, an increase in haptophyte relative abundance was observed in the Southern Ocean. Similarly, the viral fraction was dominated by members of the order Caudovirales across all stations; however, a higher presence of NCLDVs (mainly chloroviruses and mimiviruses) was observed in the Southern Ocean. To our knowledge, this is the first time that a statistical significant difference in the microbiome (from viruses to protists) on both sides of the APF. We also show that not all phylotypes can be found everywhere and that meDNA is not a suitable resource for monitoring aquatic microbial diversity.